DECREASED LEVELS OF FOLATE RECEPTOR-β AND REDUCED NUMBERS OF FETAL MACROPHAGES (HOFBAUER CELLS) IN PLACENTAS FROM PREGNANCIES WITH SEVERE PREECLAMPSIA (PE) - Tang, Zhonghua (2013)
PROBLEM: Preeclampsia (PE), a pregnancy complication of unknown etiology, is a major cause of maternal and fetal mortality and morbidity. Previous studies have described placental genes which are up-regulated in expression in PE, but few studies have addressed placental gene suppression in this syndrome. METHOD OF STUDY: Gene profiling and quantitative reverse transcription PCR (qRTPCR) analyses were used to identify genes down-regulated in placentas from women with severe preterm PE compared to gestational age-matched normotensive controls with spontaneous preterm birth (sPTB). Western blotting and immunohistochemistry were used to evaluate levels and patterns of cell type-specific protein expression in PE and sPTB group placentas. RESULTS: Levels of macrophage marker [folate receptor (FR)-β, CD163, and CD68] mRNA and FR-β protein were significantly down-regulated in PE group placentas compared to the sPTB group. Numbers of Hofbauer cells (HBCs, fetal macrophages) and FR-β protein in these cells were reduced in PE group placentas. CONCLUSION: Severe PE is associated with decreased placental expression of FR-β and a reduction in the number of HBCs. Reduced placental macrophage function is likely to play a key role in the pathophysiology of PE.